Model Transferability and Reduced Experimental Burden in Cell Culture Process Development Facilitated by Hybrid Modeling and Intensified Design of Experiments - Bayer, Benjamin; Duerkop, Mark; Striedner, Gerald; Sissolak, Bernhard (Frontiers in Bioengineering and Biotechnology, 2021)
Reliable process development is accompanied by intense experimental effort. The utilization of intensified design of experiments combined with hybrid modeling potentially reduces process development burden. Intensified design of experiments can provide more process response information in less overall process time whereas hybrid modeling serves as commodity to describe this behavior the best way. Therefore, a combination of both approaches appears beneficial, for faster design screening and is especially of interest at larger scales where the costs per experiment raise significantly. Ideally, profound process knowledge is gathered at a small scale and only complemented with few validation experiments on a larger scale, saving valuable resources. In this work, the transferability of hybrid modeling for Chinese hamster ovary cell bioprocess development along scale was investigated. A two-dimensional DoE was fully characterized in shake flask duplicates (300 mL), containing three different levels for the cultivation temperature and the glucose concentration in the feed. Based on this data, a hybrid model was developed and its performance on estimating the viable cell concentration and product titer in 15 L bioprocesses with the same DoE settings was assessed. To challenge the modeling approach, 15 L bioprocesses also comprised intensified DoE runs with intra-experimental CPP shifts, increasing process dynamics. Subsequently, also the applicability of the intensified DoE cultivations to estimate the static cultivations was investigated. The shaker-scale hybrid model proved suitable for application to 15 L-scale (1:50), estimating the viable cell concentration and the product titer with an NRMSE of 10.92 % and 17.79 %, respectively. Additionally, the intensified DoE hybrid model performed comparable, displaying NRMSE values of 13.75 % and 21.13 %. The low errors when transferring the models from shaker to reactor and between the DoE and the intensified DoE approach highlight the suitability of hybrid modeling for mammalian cell culture bioprocess development and the potential of intensified DoE to accelerate process characterization and improved process understanding.